ANALYSIS OF ENGINEERING AND GEOLOGICAL CONDITIONS GORODA ASTANY FOR CALCULATION OF BASIS AND FUNDAMENTOV ZDANIY AND SOORUZHENIY - Tulegenov M.B., Тулегенов М.Б. (Рroblems of engineering and professional education, 2023)
In practice of actual engineering there is often the question of the model calculation and design bases and foundations of buildings and structures taking into account the peculiarities of engineering-geological conditions of a particular locality. In the construction of buildings and structures in Astana pile is widely used. Justifying the construction of pile foundations requires efficient production of piling works and the correct assessment of the bearing capacity of foundation soils.